Análisis de sistemas de tratamiento de aguas residuales en la industria del curtido de pieles - Ilbay Caguana, Jhonatan Iván (2021)
Tanning is the process of transforming the skin of animals (bovine, pig, and sheep) into a finished product known as leather. Tanning as an economic activity generates job opportunities as well as boosts the economy of the country. At the national level, the process of leather tanning results out of two methods. The use of chromium salts and vegetable agents, from which wastewater containing toxic chemical components with a high content of bioburden is derived, and therefore, it is crucial to provide an adequate treatment system. This research aimed to study the productive processes of the leather tanning industry that are applied in Ecuador and determine which would be the most suitable basic treatment system for this sector, according to the average characteristics of the generated effluents. To achieve the aim of this study, bibliographic research was carried out supported by scientific databases, which allowed estimating the levels of contamination of the wastewater of the national tanneries and proposing a purification system based on primary and secondary treatment stages. Effectiveness was verified with the application of theoretical performance balances. The exposed procedure shows that all tanneries can apply treatments according to their production processes and their residuals. It is essential in this type of effluents to maintain control of the pre-treatment and use it separately to the two main production lines: tanning and peeling